An autopsy report of accidental burial in a beach sand hole. (November 2018) - Kiryu, Kyoka; Takeichi, Toshiaki; Kitamura, Osamu
Highlights: Aspiration of sand is a major contributing factor in asphyxia after accidental burials. Sand mass induces asphyxia by compressing the chest. Beach sand hole excavations should be recognized as life-threatening events. Abstract: We present a 23-year-old married couple who died by accidental burial in a beach sand hole. The victims fell into a hole that had been covered with a plastic sheet, and were buried suddenly by sand that had been piled on the top of the sheet. At autopsy, facial congestion; petechial hemorrhages in the conjunctivae and the oral mucosa; skin petechiae at the face, neck and upper chest; congestion and hemorrhages in the cervical lymph nodes; and some minor hemorrhages in the cervical muscles were found in both victims. Little sand was evident in the airway, while sand debris was found in the oral cavity. Prior reports suggest that aspiration of sand is a major contributing factor in asphyxia after accidental burials. However, neck and chest compression and face coverage by sand masses could induce lethal asphyxia without airway obstruction caused by sand aspiration. Asphyxia was deemed to be the cause of death in both individuals and was considered to result from chest compression by sand. In addition, compression of the neck may also have contributed to asphyxia. In this instance, the sand beach hole was excavated for recreational purposes. The potentially life-threatening implications of beach sand hole excavations should be recognized and highlighted to prevent lethal accidents such as those described in this report.